Neural correlates underlying musical semantic memory - Groussard, Michèle (New York Academy of Sciences, Blackwell, 2009)
Numerous functional imaging studies have examined the neural basis of semantic memory mainly using verbal and visuo-spatial materials. Yet, musical material allows an original way to explore semantic memory processes. We used PET imaging to determine the neural substrates that underlie musical semantic memory using different tasks and stimuli. The results of 3 PET studies revealed a greater involvement of the anterior part of the temporal lobe. Concerning clinical observations and our neuroimaging data, the musical lexicon (and most widely musical semantic memory) appears to be sustained by a temporo-prefrontal cerebral network involving right and left cerebral regions.